Simple Shear Behaviour of Sarawak Alluvium - Nur Khairunnisa, Ismail (Universiti Malaysia Sarawak, 2024)
This study examines the behaviour of tropical alluvial soils, focusing on their simple shear characteristics and inherent anisotropy. The research addresses the limited understanding of these soils, which exhibit unconventional engineering properties. Direct simple shear (DSS) tests performed on 52 undisturbed soil specimens cut in both horizontal and vertical orientations, alongside cyclic direct simple shear (CyDSS) tests on 16 specimens. The analysis revealed variations in index properties, with silt content prevailing over clay content. The DSS tests showed a typical stress-strain relationship, where shear strength increased until failure, followed by a reduction in strength. Pore water pressure increased with strain, reaching notable levels during testing. A relationship between undrained shear strength and over consolidation ratio (OCR) identified, with negligible differences in shear strength between orientations; however, vertically cut samples exhibited higher random errors. Microfabric analysis indicated a low preferred particle orientation, challenging the assumption of high anisotropy. Cyclic shearing tests revealed hysteresis loops with decreasing shear stress as cycles progressed. Excess pore water pressures correlated with displacement levels, while the damping ratio increased with shear strain but decreased with the number of cycles. The normalized shear modulus consistently decreased with increasing shear strain and loading cycles. These findings enhance the understanding of the strength behaviour and anisotropic characteristics of tropical alluvial soils.